Szanse i zagrożenia rozwoju agroturystyki na terenach wschodnich gmin przygranicznych - Jeleń, Bogusław (Chances and Dangers of Development of Agritourism on Eastern Terrains of Border Commune, 2006)
The author presents attractions and abilities of agritourism development in eastern, border territory of communes. These communes are situated at the border of the Bug Euroregion. It makes chances of economic revival e.g. by international transport service. Here is an eastern border of the European Union, which makes arrival for tourists from Western Europe countries easier. The study presents strong and weak sides of agritourism development in this part of the country. The author also presents chances and threats connected with this progress.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 348-353